Sunday
March 26, 2017

Post a New Question

Posted by on .

Can any one help me with this problem am having trouble with coming up with the answer. 7-(-1)/3(2)-9/(-3)

  • math - ,

    It depends on how the terms are groups shown by parentheses and/or brackets. It makes things clearer, if you put spaces between the terms, as I did below.

    7 - (-1)/3(2) - 9/(-3) = 7+1/6 + 3 = 10 1/6

    [7-(-1)]/3(2) - 9/(-3) = 8/6 + 3 = 4 2/3

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question